Identifying playing styles of european soccer teams during the key moments of the game - Plakias, S.; Kokkotis, C.; Moustakidis, S.; Tsatalas, T.; Papalexi, M.; Kasioura, C.; Giakas, G.; Tsaopoulos, D. (Journal of Physical Education and Sport, 2023)
Performance analysis considerably contributes to improving performance in sports. Therefore, researchers have increased their interest in sports analytics. In football in particular, playing styles are the subject of extensive research. Identifying and measuring different playing styles that soccer teams can adopt during a match is a very important step toward a more effective analysis of opponents, own team post-match analysis, and recruiting players. Specifically, it has been a great challenge to identify and classify playing styles in football during all phases of the game (i.e., during key moments and sub-phases of the game). Therefore, the aim of this study is to recognize and quantify distinct playing styles in European soccer leagues. In achieving this, a wide range of competitions and variables were used. Data were collected from 2999 league matches (5998 observations) in 11 different countries during the 2021-22 season. Factor analysis with principal component analysis (PCA) was used to analyze and group 88 performance indicators. Nineteen factors had eigenvalues greater than 1, accounting for 84.8% of the total variance. Most of the variance (49.35%) was explained by the first four factors, which are related to build-up and transitions. Sixteen out of the nineteen factors were associated with teams' playing styles. They were classified across all phases and sub-phases of the game, whereas the remaining three were related to matches. The findings of this study were classified in such a way as to provide a structured framework for analysts and coaches that can be used in the training process of all four key moments of the game.